PamulDB: a comprehensive genomic resource for the study of human- and animal-pathogenic Pasteurella multocida. (25th February 2019) - Li, Tian; Xu, Xiao-Fei; Du, Hui-Hui; Li, Li; Li, Neng-Zhang; Zhou, Ze-Yang; Peng, Yuan-Yi
Abstract: Pasteurella multocida can infect a wide range of host, including humans and animals of economic importance. Genomics studies on the pathogen have produced a large amount of omics data, which are deposited in GenBank but lacks a dedicated and comprehensive resource for further analysis and integration so that need to be brought together centrally in a coherent and systematic manner. Here we have collected the genomic data for 176 P. multocida strains that are categorized into 11 host groups and 9 serotype groups, and developed the open-access P. multocida Database (PamulDB) to make this resource readily available. The PamulDB implements and integrates Chado for genome data management, Drupal for web content management, and bioinformatics tools like NCBI BLAST, HMMER, PSORTb and OrthoMCL for data analysis. All the P. multocida genomes have been further annotated for search and analysis of homologous sequence, phylogeny, gene ontology, transposon, protein subcellular localization and secreted protein. Transcriptomic data of P. multocida are also selectively adopted for gene expression analysis. The PamulDB has been developing and improving to better aid researchers with identifying and classifying of pathogens, dissecting mechanisms of the pathogen infection and host response.